О "СИНТЕТИЧЕСКОЙ" ГЕОМОРФОЛОГИИ (К 40-ЛЕТИЮ МОРФОМЕТРИЧЕСКОГО МЕТОДА) - Лобанов В.В. (My University, 2003)
Valley's order is the synthetic notion that integrates process, matter and time of relief formation. Making of landforms has three stage: juvenile (bedded dynamic phase), mature (perstrative phase), senile (constrative phase). The full complex of evolution stages corresponds to the contents of the notion "valley's order". All this may be named as "law of Davis - Lamakin". The notion of valley's order may serve as the measure of age of relief.
Keywords: 551.4.01